How do you solve #(x+1)/3 = (x-1)/4#?

2 Answers
Jun 5, 2016

Answer:

x=-7

Explanation:

4(x+1)=3(x-1)
4x+4=3x-3
4x-3x=-4-3
x=-7

Jun 5, 2016

Answer:

#x=-7#

Explanation:

In the equation #(x+1)/3=(x-1)/4#, let us first multiply both sides by LCD of #3# and #4# i.e. #12# to eliminate fractions.

Hence this equation can be written as

#(x+1)/3xx12=(x-1)/4xx12#

#4(x+1)=3(x-1)# or

#4x+4=3x-3#

now transposing terms containing variable #x# to left hand side and constant terms to right hand side, we get

#4x-3x=-3-4# or

#x=-7#